Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/cncr.21967
|View full text |Cite
|
Sign up to set email alerts
|

Role of fluorine‐18 fluoro‐deoxyglucose positron emission tomography scan in the evaluation and follow‐up of patients with low‐grade lymphomas

Abstract: BACKGROUND Fluorine‐18 fluoro‐deoxyglucose positron emission tomography (FDG‐PET) scanning has excellent sensitivity and specificity for staging non‐Hodgkin lymphomas, but to the authors' knowledge few studies to date have evaluated FDG‐PET in low‐grade lymphomas only. METHODS A retrospective study was performed on patients with biopsy‐proven nontransformed and transformed follicular lymphoma (FL), B‐cell small‐cell lymphocytic lymphoma (SLL/CLL), or marginal zone lymphoma (MZL) who underwent PET and computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
145
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 196 publications
(155 citation statements)
references
References 21 publications
6
145
3
1
Order By: Relevance
“…17,23,24 In the current study, 18 F-FDG-PET detected disease sites with high accuracy in FL, which was in agreement with previous reports. 16,17 However, it should be noted that 18 F-FDG-PET failed to detect sites in all 3 patients who had FL in the duodenum. Hoffmann et al reported similar results in 7 patients with primary duodenal FL.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…17,23,24 In the current study, 18 F-FDG-PET detected disease sites with high accuracy in FL, which was in agreement with previous reports. 16,17 However, it should be noted that 18 F-FDG-PET failed to detect sites in all 3 patients who had FL in the duodenum. Hoffmann et al reported similar results in 7 patients with primary duodenal FL.…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to the clinical observation that outcomes do not differ significantly between these 2 categories. 17 However, this information would be important for patients with grade 3 FL, because it is believed that these patients to have a more aggressive clinical course and to need more aggressive treatment. However, neither the disease site detection rate nor the SUV differed between grade 3 and grades 1 or 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopic primary tumors as the one presented here likely account for many PET false negatives. The reported PET accuracy in detecting CLL/SLL is even lower [29]. None of the two neoplasms were identified by PET in our patient, either at the primary site or in the cervical lymph nodes.…”
Section: Discussioncontrasting
confidence: 55%
“…Published literature includes 10 retrospective analyses [9][10][11][12][13][14][15][16][17][18] and 1 prospective one [19]: pooled analysis of 356 patients revealed that 24% were upstaged from Stage I-II to Stage III-IV. Baseline PET also showed to have a high prognostic value, irrespective of FLIPI [10,11,17,19].…”
Section: Issue 1: Staging (Consensus-based Recommendations)mentioning
confidence: 99%